Impact of the Seeding Method on Physiological, Agronomic, and Biochemical Performance of Sesame (Sesamum indicum L.) Varieties Grown in Burkina Faso - Badiel Badoua; Kihindo Adama Pascal; Yao Koffi Bertin; Nana Rasmata; Ouedraogo Razacswendé Fanta; Dondasse Edmond; Tamini Zoumbiessé (International Journal of Agronomy)
In Burkina Faso, the sesame sector is still relatively unorganized, with poor quality seeds that are unsuitable or outdated farming practices and noncompliant with recommended technical itineraries. This situation is very worrying and needs to be rectified. For this reason, we undertook this study to highlight the impact of the seeding method on the physiological, morphological, and agronomic performances of sesame (Sesamum indicum L.) varieties grown in Burkina Faso. The experiment was conducted at the Gampèla agropedagogical station located at 12°25′N, 12°22′W from Ouagadougou. Varieties S-42, 32-15, Wollega, and Humera were grown in strips (broadcast seeding) and in randomized complete blocks (row sowing). Row seeding favored plant growth and development for all varieties. Seed yield per plant for row seeding was significantly (P<0.001) higher than for broadcast seeding. In terms of 1000 seed weight, there was a decrease in the Wollega variety (2.42 g) in the broadcast seeding group compared with the row seeding group (3.13 g). The seeding method had no effect on the other varieties. The seeding method also had no significant influence on the lipid and protein contents of the seeds. When sown in rows, varieties S-42 (25.7 g/kg), 32-15 (20.64 g/kg), and Wollega (17.33 g/kg) accumulated more K than the broadcast seeding groups. For the Humera variety, the seeding method had no effect on K. Na accumulation in leaves was statistically equal for all varieties in both broadcast and row seeding. Variety 32-15 accumulated more Mg when sown broadcast (5.95 g/kg) than when sown in rows (3.85 g/kg). On the other hand, the varieties S-42 (3.13 g/kg), Wollega (4.21 g/kg), and Humera (3.12 g/kg) accumulated less Mg when broadcast than when sown in rows (S-42 (4.37 g/kg), Wollega (5.68 g/kg), and Humera (5.73 g/kg)). Thus, seeding in rows is recommended to obtain better vegetative development and higher capsule and seed yields for all varieties. Both of the seeding methods deliver the same lipid, protein, and Na contents for all varieties. Broadcast seeding is recommended for better Mg content for variety 32-15, and row seeding is recommended for better K content for varieties S-42, Wollega, and 32-15.